Legal Disputes in Business Law Practice in Indonesia - Diana, Laila; Meilani, Devi Putri; Benita, Marsya; Safina, Ama; Arizal, Arizal; Imran, Ali; Ivo, Astri; Andikos, Adi Fitra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Commercial law in Indonesia is an essential instrument to ensure certainty and fairness in economic activities. However, in practice, legal disputes often arise due to contractual default, breach of agreement, bankruptcy, and unfair business competition. This study aims to analyze the causes of legal disputes in the practice of commercial law in Indonesia and the mechanisms for their resolution. The research method employed is a normative juridical approach by analyzing legislation, legal doctrines, and court decisions. The findings indicate that although litigation and non-litigation mechanisms are available, the effectiveness of dispute resolution is still influenced by the integrity of legal enforcers, the quality of contracts, and the legal awareness of business actors. Therefore, commercial law reform and the strengthening of dispute resolution institutions are necessary to create a healthy business climate.